Comparative Study of Antioxidant and Antibacterial Activities of Tropical Citrus Fruits (Juice and Peels) - Julfi Restu Amelia; Fildzah Hashfi Safitri; Giyatmi Giyatmi; Intan Nurul Azni (The University of Lampung, 2024)
Tropical citrus fruits contain important bioactive compounds with health-promoting properties such as antioxidant and antibacterial properties. This study provided comparative data on the antioxidant and antimicrobial activity of tropical citrus (local lemons, imported lemons, and limes) juice and peel. Antioxidant activity of citrus fruits was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and expressed as IC50. Antimicrobial activity was evaluated against pathogens (E. coli, B. subtilis, S. aureus) using agar diffusion method. The results showed that very strong antioxidants were detected in domestic and imported lemon juice (33.45 ppm; 31.43 ppm) and peel (15.89 ppm; 44.50 ppm). However, lime juice and peel had stronger antioxidant activity (60.35 ppm and 59.54 ppm). The highest zone of inhibition was observed against S. aureus and the lowest was recorded against E. coli. The diameters of the zones of inhibition of local lemon, imported lemon, and lime juice against S. aureus were 26.40 mm, 27.95 mm, and 27.31 mm; E. coli was 15.64 mm, 16.84 mm, and 16.63 mm; and B. subtilis was 17.88 mm, 21.77 mm, and 21.24 mm, respectively. Tropical citrus juice showed higher activity against Grampositive than Gram-negative bacteria tested. Local lemon, imported lemon, and lime peels did not inhibit E. coli, B. subtilis, and S. aureus. Keywords: Antibacterial, Antioxidant, Lemon, limes, Tropical citrus